Cyclodextrin stabilisation of steroid against microbial degradation - S. M. Khomutov; G. V. Sukhodol'skaya; M. V. Donova (ՀՀ ԳԱԱ հրատ.)
Microbial degradation of hydroxy androstenedione in solutions of methylated cyclodextrin was investigated.
Keywords: Biology; Biochemistry; Pharmacology